2021
DOI: 10.3390/ijms22083955
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensation and Mechanotransduction by Lymphatic Endothelial Cells Act as Important Regulators of Lymphatic Development and Function

Abstract: Our understanding of the function and development of the lymphatic system is expanding rapidly due to the identification of specific molecular markers and the availability of novel genetic approaches. In connection, it has been demonstrated that mechanical forces contribute to the endothelial cell fate commitment and play a critical role in influencing lymphatic endothelial cell shape and alignment by promoting sprouting, development, maturation of the lymphatic network, and coordinating lymphatic valve morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 226 publications
(212 reference statements)
0
6
0
Order By: Relevance
“…Emerging evidence suggests that neutrophils may also interact with the lymphatic system by regulating lymphangiogenesis (or growth of new lymphatic vessels) in inflamed tissues and lymph nodes during inflammation and cancer progression [3,95]. Recent studies have identified signals which promote the formation of the lymphatic vasculature [96,97]. Vascular endothelial growth factors, such as VEGF-A, VEGF-C and VEGF-D can induce LEC sprouting and proliferation.…”
Section: Neutrophil Contributions To Lymphangiogenesismentioning
confidence: 99%
“…Emerging evidence suggests that neutrophils may also interact with the lymphatic system by regulating lymphangiogenesis (or growth of new lymphatic vessels) in inflamed tissues and lymph nodes during inflammation and cancer progression [3,95]. Recent studies have identified signals which promote the formation of the lymphatic vasculature [96,97]. Vascular endothelial growth factors, such as VEGF-A, VEGF-C and VEGF-D can induce LEC sprouting and proliferation.…”
Section: Neutrophil Contributions To Lymphangiogenesismentioning
confidence: 99%
“…The lymphatic system, composed of lymph nodes, lymph ducts and lymphatic vessels, plays an important role in maintaining interstitial fluid homeostasis through intestinal water and macromolecules absorption and returning them back to the bloodstream [ 1 ]. Lymphangiogenesis, the generation of new lymphatic vessels from the preexisted ones, occurs during pathological conditions including in inflammation and cancer progression [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the lymphatic system begins to develop between the 6th and 7th week of pregnancy, whereas in mice it appears around the embryonic day 10 (E10.0). The wellknown homeobox transcription factor Prox1 (Prospero homeobox 1) [75] and the growth factor VEGFC (Vascular endothelial growth factor C) [76] are typical LECs markers, playing a critical role in lymphatic vessels prenatal sprouting from embryonic veins and maturation [77,78]. Prox1 upregulates the expression of lymphatic-specific genes in LECs acting as a master regulatory gene leading to lymphatic commitment and maintenance [79,80].…”
Section: Lymphatic Vessels Of Airways and Lungsmentioning
confidence: 99%